Implementasi Pembelajaran Berdiferensiasi pada Kelas Inklusif di Madrasah Ibtidaiyah - Asrorudin Asrorudin; Ria Nurhayati (Auladuna: Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aims to analyze the implementation of differentiated instruction in inclusive classrooms at Madrasah Ibtidaiyah, and to identify the supporting and inhibiting factors influencing its implementation. The research employed a qualitative approach using a descriptive case study design. The research participants included classroom teachers of grades II, III, and V, the school principal, and students with special educational needs. Data were collected through classroom observations, semi-structured interviews, and document analysis, and were analyzed using the interactive model of Miles and Huberman, involving data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation, technique triangulation, and member checking. The findings reveal that differentiated instruction was implemented through adjustments in content, process, product, and learning environment. Teachers simplified learning materials for slow learners, provided concise and step-by-step instructions for students with ADHD, and offered alternative task formats for students with anxiety disorders. Differentiation was also reflected in flexible grouping, scaffolding strategies, positive reinforcement, modified assessment standards, and flexible time allocation. Supporting factors included teachers’ commitment, active communication with parents, and an inclusive school culture. Meanwhile, limitations in supporting facilities and the absence of permanent special assistant teachers were identified as inhibiting factors. The study concludes that differentiated instruction serves as an effective pedagogical strategy to promote participatory and adaptive inclusive education in Islamic elementary schools.